STRATEGI PENGGALANGAN DANA UNTUK PENDIDIKAN : Studi Penggalangan Dana ZIS Rumah Zakat dan Lembaga Pengembangan Insani Dompet Dhu’afa Untuk Penyelenggaraan Pendidikan Berkualitas - Fahrurrozi Fahrurrozi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
This research is based on three main problems. First, national education challenge related to the quality and equality distribution of education ; second, the importance of financial resource for creating an effective education; and third, the existence of two amil institutions which have been being establishing education up to standard and not taking any payment from students. Based on the rationale above, the main problem of this research is how the fundraising strategy conducted by Rumah Zakat dan Lembaga Pengembangan Insani Dompet Dhu’afa for implementing the qualified formal education. Then four main objectives of the research are to explore and analyze the philosophy of fundraising conducted by Rumah Zakat and Lembaga Pengembangan Insani ; the fundraising program stated by Rumah Zakat and Lembaga Pengembangan Insani ; the implementation of fundraising conducted by Rumah Zakat and Lembaga Pengembangan Insani ; and to explore and analyze the impact of fundraising to the implementation of qualified formal education.